CAR T cell therapy becomes CHIC: “cytokine help intensified CAR” T cells - Thomas, Simone; Abken, Hinrich (Frontiers in Immunology, 2023)
Chimeric antigen receptors (CARs) in the canonical “second generation” format provide two signals for inducing T cell effector functions; the primary “signal-1” is provided through the TCR CD3 chain and the “signal-2” through a linked costimulatory domain to augment activation. While therapy with second generation CAR T cells can induce remissions of leukemia/lymphoma in a spectacular fashion, CAR T cell persistence is frequently limited which is thought to be due to timely limited activation. Following the “three-signal” dogma for inducing a sustained T cell response, cytokines were supplemented to provide “signal-3” to CAR T cells. Recent progress in the understanding of structural biology and receptor signaling has allowed to engineer cytokines for more selective, fine-tuned stimulation of CAR T cells including an artificial autocrine loop of a transgenic cytokine, a cytokine anchored to the CAR T cell membrane or inserted into the extracellular CAR domain, and a cytokine receptor signaling moiety co-expressed with the CAR or inserted into the CAR endodomain. Here we discuss the recent strategies and options for engineering such “cytokine help intensified CAR” (CHIC) T cells for use in adoptive cell therapy.